Pengaruh Lama Perawatan Terhadap Indeks Platelet Pasien Demam Berdarah Dengue (Dbd) Di Rumah Sakit Islam Jemursari Surabaya - Gilang Nugraha; Wieke Sriwulan; Ruri Arinil Khoiro (UNUSA Press, 2021)
Dengue Hemorrhagic Fever (DHF) is one of the most tropical infectious diseases in Indonesia caused by dengue virus and mediated by the bites of Aedes aegypti and Aedes albopictus mosquitoes. One of the clinical symptoms of dengue disease is a decrease in the number of blood platelets. There are several platelet indices that are known as indicators of platelet activation, namely Mean Platelet Volume (MPV), and Platelet Distribution Width (PDW). DHF patients who experience treatment at the hospital only monitor the low platelet count in healing. The purpose of this study was to determine the effect of length of treatment on the MPV Platelet Index and PDW of DHF patients. Data was obtained by taking primary data at Jemursari Islamic Hospital Surabaya. This research is an One Shot Case Studies research with description analitic method and Cross sectional design in DHF patients at Jemursari Islamic Hospital Surabaya. The sampling technique uses accidental sampling technique. Analysis of MPV and PDW data using the Wilcoxon Sign Rank Test non-parametric test. The test was used to see the effect of patient length of care on the MPV and PDW platelet index with a significance level of α = 0.05. The results of the Wilcoxon Signk Rank Test on the MPV show a significance of (ρ = 0.845), and the results of the Wilcoxon Signk Rank Test statistic on the PDW show a significance of (ρ = 0.469). Based on the results of the study, it can be concluded that there is no effect on the length of treatment on the MPV and PDW Platelet Index in DHF patients at Jemursari Hospital Surabaya.